2018
DOI: 10.1080/10643389.2018.1531688
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying ecological risks of aquatic micro- and nanoplastic

Abstract: Diverse effects of nano-and microplastic (NMP) have been demonstrated in the laboratory. We provide a broad review of current knowledge on occurrence, measurement, modeling approaches, fate, exposure, effects, and effect thresholds as regard to microplastics in the aquatic environment. Using this information, we perform a 'proof of concept' risk assessment for NMP, accounting for the diversity of the material. New data is included showing how bioturbation affects exposure, and exposure is evaluated based on li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
260
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 381 publications
(285 citation statements)
references
References 145 publications
5
260
3
Order By: Relevance
“…Hence, microplastics are largely a transitionary state between macrodebris and nanomaterials. Besseling et al () estimated that fragmentation of spherical microplastics could generate >10 14 times greater numbers of nanoparticles. To understand microplastic sources, fate, and consequences, one must consider the continuum, from plastic products/debris to microplastics and nanoplastics.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, microplastics are largely a transitionary state between macrodebris and nanomaterials. Besseling et al () estimated that fragmentation of spherical microplastics could generate >10 14 times greater numbers of nanoparticles. To understand microplastic sources, fate, and consequences, one must consider the continuum, from plastic products/debris to microplastics and nanoplastics.…”
Section: Overviewmentioning
confidence: 99%
“…Some authors (e.g., Besseling et al, ; Koelmans et al, ) have suggested that the importance of contaminant accumulation potential may be overestimated). They hypothesized that the outcome varies depending on the conditions within the gut of the organism studied, that is, the type of gut fluid (Tanaka et al, ).…”
Section: Microplastic Uptake and Consequences In Biotamentioning
confidence: 99%
“…The ability of freshwater benthic macroinvertebrates to ingest MP depends on species characteristics such as their feeding habit or developmental stage (5,6), as well as on plastic particle properties and environmental conditions (7). Single-species laboratory studies have found that the ingestion of MP by freshwater benthic macroinvertebrates can cause adverse effects (8)(9)(10), which also seems to differ among species. For instance, a reduction in the growth of the amphipod Gammarus pulex was found after a 28-day exposure to polystyrene MP, while five other benthic macroinvertebrates were not affected under the same experimental conditions (6).…”
Section: Introductionmentioning
confidence: 99%
“…Although it is possible to detect the presence of sub‐micron plastic particles in environmental samples using pyrolysis GC–MS (Ter Halle et al ., ), the confounding influence of other environmental components currently hinders the direct quantification of plastic nanoparticles in environmental samples. In contrast to nanoplastics, microplastics (100 nm‑5 mm) have been well quantified in various marine environments, with the highest concentrations recorded in beach sediments (Besseling et al ., ). As this plastic degrades into nanoparticles, it can be assumed that the highest concentrations of nanoparticles will be achieved in areas rich in plastic debris with little mixing to the wider environment.…”
Section: Resultsmentioning
confidence: 97%